ANALISIS FRAMING BERITA KEKERASAN SEKSUAL PADA ANAK DI LUWU TIMUR DARI MEDIA KOMPAS.COM DAN LIPUTAN6.COM - Gina Rae Raehani (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
Abstract: News is an easy source of information. In the process of writing, news according to the needs and the media. The news of sexual violence that is being widely disseminated is the sexual violence that befell three children in East Luwu. As of now, the news is still under investigation. Researchers are interesting with the news. The purpose of this study is to find out the framing analysis of the media Kompas.com and Liputan6.com in packaging the news of sexual violence that befell three children in East Luwu. The method used in this analysis is descriptive qualitative method. While the theory that supports the research is the Zhingdang Pan and Gerald M Kosicki model. The results of this analysis are: 1) knowing the differences in news writing of the two media 2) knowing the comparison and framing used by the second media. Keywoards: news, framing, sexual assault